Analisis Efektivitas Pengelolaan dan Pendistribusian Zakat dalam Mengurangi Kemiskinan Melalui Program Pemberdayaan Ekonomi pada BAZNAS Kota Batu : Pendekatan Kuantitatif - Aulia, Nur Afifa; Hakim, Rahmad; Hakim, Arif Lukman; Noviyanti, Ririn (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The problem of poverty in the city of Batu is still exist which motivated by several factors due to the low provision of zakat, infaq and alms funds collected from the community through BAZNAS Batu City. The aim of this research is to see the effectiveness of zakat management and distribution carried out by BAZNAS Batu City. In this research, a quantitative method was used with a significance test approach. The population and sample in this study were 51 respondents using data collection techniques through questionnaires and data analysis using the Eviews 12 application. The results of the study stated that there is an economic empowerment program by BAZNAS Batu City. In helping to alleviate poverty in the people of Batu City, BAZNAS is recorded as running an economic empowerment program in twenty-three villages with various business assistance that has been distributed. The program of BAZNAS’ zakat empowerment in Batu City had a significance number of 0.0001 with significance criteria below 0.05, while the significance number for zakat distribution was 0.000 with the criteria significance below 0.05. Thus, the management and distribution of zakat at BAZNAS Batu City has a significant effect in reducing poverty. This is also supported by the change in position of mustahiq who have experienced economic development to become muzzaki at BAZNAS Batu City.